2013
DOI: 10.1111/psyp.12050
|View full text |Cite
|
Sign up to set email alerts
|

The “red‐alert” effect in visual search: Evidence from human electrophysiology

Abstract: Participants had to determine the orientation of a segment inside a target color circle among other gray distractor circles. The target circle was either red or green and was accompanied in the display by a distractor in the other color. To dissociate event-related potentials of target and distractor processing, one of them was on the vertical meridian and the other in a lateral position. In Experiment 1, the target color was indicated on a per-trial basis and, in Experiment 2, on a per-block basis. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 28 publications
4
39
0
Order By: Relevance
“…The suggestion that appears to emerge from these studies is that of a consistent link between inhibition/excitation of neurons in the occipitoparietal cortex (e.g., Prime & Jolicœur, ) and the polarity of ERP components held to reflect the activity of such neurons. More specifically, these findings suggest that target activation enhancement is often reflected in a contralateral increment in negativity accompanied by an increment in positivity, held to reflect suppression, contralateral to distractors when such stimuli are displayed in distinct visual hemifields, with these reflections usually unfolding in a 80–300 ms time range after eliciting stimulus (Fortier‐Gauthier, Dell'Acqua, & Jolicœur, ; Hickey et al., ; Sawaki & Luck, ), giving rise to N1‐N2pc ERLs as those described in the present circumstances. In addition, a contralateral posterior positivity in a window of 130–160 ms, coined Ppc, is also often observed when a salient stimulus is presented in one hemifield accompanied by a luminance‐matched distractor in the other hemifield (e.g., Corriveau et al., ).…”
Section: Discussionmentioning
confidence: 80%
“…The suggestion that appears to emerge from these studies is that of a consistent link between inhibition/excitation of neurons in the occipitoparietal cortex (e.g., Prime & Jolicœur, ) and the polarity of ERP components held to reflect the activity of such neurons. More specifically, these findings suggest that target activation enhancement is often reflected in a contralateral increment in negativity accompanied by an increment in positivity, held to reflect suppression, contralateral to distractors when such stimuli are displayed in distinct visual hemifields, with these reflections usually unfolding in a 80–300 ms time range after eliciting stimulus (Fortier‐Gauthier, Dell'Acqua, & Jolicœur, ; Hickey et al., ; Sawaki & Luck, ), giving rise to N1‐N2pc ERLs as those described in the present circumstances. In addition, a contralateral posterior positivity in a window of 130–160 ms, coined Ppc, is also often observed when a salient stimulus is presented in one hemifield accompanied by a luminance‐matched distractor in the other hemifield (e.g., Corriveau et al., ).…”
Section: Discussionmentioning
confidence: 80%
“…Fortier‐Gauthier, Dell'Acqua, & Jolicœur () recently found that the color of the object that elicits the lateralized ERP influences whether a contralateral positivity is observed in the waveform. In their paradigm, both the target and distractor were color singletons, and participants responded to the orientation of a line contained within the target color singleton.…”
Section: Discussionmentioning
confidence: 99%
“…First, in the target‐distractor variant, both the target and distractor are color singletons. In the typical paradigm, the target is a shape or color singleton and the distractor is a singleton of the other type (see Fortier‐Gauthier et al., , for an exception). Second, in the target‐distractor variant, participants must discriminate the orientation of the color singleton letter T and the distractor is a color singleton letter L (i.e., the target is defined by spatial configuration).…”
Section: Discussionmentioning
confidence: 99%
“…In Experiment 1, we tested whether attention is biased to the physical or relative target color when the target and target context colors are fixed. To ensure a generalization of our results and to exclude potential confounds by color‐specific search asymmetries (e.g., Fortier‐Gauthier, Dell'Acqua, & Jolicoeur, ), one group of observers searched for a unique orange target (singleton target) among three yellow context items (relative task set: redder; physical task set: orange), whereas a different group of observers searched for an orange singleton among three red nontargets (relative task set: yellower; physical task set: orange; Figure ). Search displays were preceded randomly by one out of four possible types of cue arrays: (1) In perfectly matching (PERF) cue displays, the colors were identical to those of the search displays.…”
Section: Methodsmentioning
confidence: 99%